“We’re all Squares on a Screen”: Interpersonal and Intrapersonal Opportunities and Limitations of Online Intergroup Dialogue - Jackson, Grant; Schiffecker, Sarah; Poquet, Oleksandra (Online Learning, 2025)
Postsecondary institutions are seeing the need and searching for ways to prepare their students for life in an increasingly complex and often polarized society. Since its development in the late 1980s, intergroup dialogue (IGD) has become a prominent dialogic pedagogy that brings together small, diverse groups of college students to dialogue on topics related to diversity, equity, equality, and belonging. Though IGD has traditionally been an in-person experience, postsecondary institutions were required to offer IGD online during the COVID-19 pandemic, making it important to discern what opportunities and limitations may come with such online delivery. Guided by theories of intergroup contact and intergroup dialogue, we interviewed 16 college students who had participated in IGD via Zoom regarding their online IGD experience, illuminating a variety of opportunities and limitations that are interpersonal and intrapersonal in nature. Emergent themes, along with their implications for IGD theory, practice, and future research, are discussed.